Socially useless? The crucial contribution of finance to economic life - Philip Booth; Diego Zuluaga (Institute of Economic Affairs (IEA), 2018)
Animosity towards the business of finance is ancient and persistent. As finance creates intangible value, its contribution is invisible to many observers, but the proposed remedy - increased statutory regulation - may heighten, rather than mitigate the exposure of taxpayers and households to recessions and speculative bubbles. Financial firms serve many useful functions, which individuals and households could scarcely undertake on their own: maturity transformation, matching lenders and borrowers at low cost, facilitating the transfer of risk and consumption across time and between people, monitoring, and diversification of investments. Banks reduce the transaction costs of financial activity, enabling people to spend their time more productively. Gross value added (GVA) by the UK financial sector amounted to 124 billion in 2016. Of this, 50% is exported. Contrary to the claims of critics, the sales and trading activity, alleged to be self-serving, accounts at most for 10% to 13% of financial services business in Britain. It is often argued that private-sector finance is short-term oriented. Whilst there is evidence that shareholders may be heavily discounting distant profits, the reasons for this could be policy uncertainty, and not irrationality. Moreover, the valuations of tech firms - whose positive cash flows lie far in the future - and low yields on corporate bonds suggest that investors are patient by historical standards. Much financial regulation assumes that providers 'dupe' consumers. But regulatory intervention is grossly miscalculated. The Financial Conduct Authority's recent interest cap on payday loans shrank the market by between three and five times more than the regulator expected. Markets are not perfect, but regulation is often a poor substitute. The much-cited literature linking financial growth and adverse economic outcomes is simply too crude to warrant drawing clear policy conclusions. Studies linking financialisation with inequality are similarly ambiguous: the top ten countries for their share of finance in GDP are a mixture of high-, medium- and low-inequality countries. Complex financial instruments and speculation, both unpopular in the wake of the 2008 crash, are not harmful on their own. In fact, they transfer risks to those who can best bear it, whilst giving greater income certainty to vulnerable people. Until and unless the value of finance is properly understood, public policy will fail to harness its benefits and may well endanger public welfare.
Keywords: L51; G18; G28; G38; G15; G14; G21; G22; G24; G20; G34; G32; E52; E60; E62; 330